2018
DOI: 10.1016/j.jmii.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for healthcare-associated infection caused by carbapenem-resistant Pseudomonas aeruginosa

Abstract: The worldwide CRPA prevalence has been on the raise and Taiwan has been also keeping up with the trend. Antimicrobials usage should be monitored carefully, especially with carbapenems and aminoglycoside. Clinicians should be award of and understand about the risk of CRPA infection, which increases by 1% with each hospitalization day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 27 publications
7
25
1
1
Order By: Relevance
“…In accordance with previous prospective or retrospective studies, our results confirmed that prior exposure to carbapenems was an independent risk factor for CRPA infection or colonization [7][8][9]. However, in contrast with some other studies [13,16], we did not find that the use of fluoroquinolones, or aminoglycosides was associated with increased CRPA infection or colonization.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with previous prospective or retrospective studies, our results confirmed that prior exposure to carbapenems was an independent risk factor for CRPA infection or colonization [7][8][9]. However, in contrast with some other studies [13,16], we did not find that the use of fluoroquinolones, or aminoglycosides was associated with increased CRPA infection or colonization.…”
Section: Discussionsupporting
confidence: 89%
“…Identifying risk factors for the development of CRPA acquisition is important for treatment options, and consequently, a number of risk factors for CRPA infection or colonization have been revealed in some retrospective clinical studies [7][8][9][10][11][12][13][14]. However, the conclusions were not always consistent among these studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could also lead to the production of odor and slime in food products. Reusing the ingredients stored at room temperature for few hours pose risk to consumers especially if they are immune compromised (Tsao et al, 2018). Apart from being a spoilage microorganism, Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…This could also lead to the production of odour and slime in food products. Reusing the ingredients stored at room temperature for few hours pose risk to consumers especially if they are immunocompromised [7]. Apart from being a spoilage microorganism, Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%